Transomental hernias: Multi-detector row computed tomography findings in 15 clinical cases - Tetsunobu Udaka; Takeyoshi Nishiyama; Tomoaki Ohtsuka; Nobuyuki Watanabe; Izuru Endou; Osamu Yoshida; Hiroaki Asano; Masatoshi Kubo; Hironori Kurokawa (Radiography Open, 2022)
Introduction: Transomental hernia (TOH), a type of intra-abdominal hernia formed as a result of incarceration through abdominal greater omental hiatus, is a rare disease that lacks specific physical features, which makes its preoperative diagnosis difficult. This study aims the clinical characteristics and radiological findings of 15 cases of TOH.